لغة الخطاب الدرامي الجزائري بين التنوعات اللسانية والتمثلات الثقافية- دراما السلطان عاشور العاشر – (مجلة الواحات للبحوث والدراسات, 2020)
The Arabic Drama Along With The Algerian One Is Considered To Be A  PartOfGlobalDramaOnTheTelevisionInterface,ThenOurOpinionAboutThe Algerian Drama In This Co-Text-Not To Discuss What The Algerian Arabic (Arab) Drama EssenceYet Also  Discussing Its Relationship With The  Binary (Language- Dialect) Slang And Linguistic  Diversity  At The Level Of Drama     InTheAlgerianSeries AndMoviesAsWell As The  Symbolic Framework   Connection Between The Viewer(Scene),Audiovisual Image And Reality. From The Main Problematic: How The Algerian Arabic Drama Wintess The Linguistic Diversity Resulting From The Diversity Of The Social Fabric And How Is It Represented In Terms Of Sound And Picture? Key Words- Discourse,Dramatic,Algerian,Linguistic,Cultural.